Spanish cinema 1973-2010 : auteurism, politics, landscape and memory - Delgado, Maria M.; Fiddian, Robin W. (Manchester University Press, 2013)
"This collection of essays offers a new lens through which to examine Spain's cinema production, following the decades of isolation imposed by the Franco regime. The seventeen key films analysed in the volume span a period of thirty-five years that has been crucial in the development of Spain, Spanish democracy, and Spanish cinema. These films encompass different genres (horror, thriller, melodrama, social realism, documentary), both popular (Los abrazos rotos/Broken Embraces, Vicky Cristina Barcelona) and more select art house fare (En la ciudad de Sylvia/In the City of Sylvia, El espíritu de la colmena/Spirit of the Beehive), and languages (English, as both first and second language, Basque, Spanish, Catalan, and French). The volume offers an expanded understanding of 'national' cinemas that negotiates the global co-production networks that fund the production of contemporary films in Spain. Furthermore, it provides treatments of key works by Guillermo del Toro and Lucrecia Martel, alongside an examination of the ways in which both established auteurs (Almodóvar, José Garci, Carlos Saura) and younger generations of filmmakers (Cesc Gay, Alejandro Amenábar, Iciar Bollaín) have harnessed cinematic language towards a commentary on the nation-state, wider issues of landscape, and the politics of historical and cultural memory. The result is a bold new study of the ways in which film has created new prisms (or indeed stereotypes) that have determined how Spain is positioned in the global marketplace."--P. [4] of cover.